Sulfated attapulgite for catalyzing the conversion of furfuryl alcohol to ethyl levulinate: Impacts of sulfonation on structural transformation and evolution of acidic sites on the catalyst. (December 2020) - Tian, Hongli; Shao, Yuewen; Liang, Chuanfei; Xu, Qing; Zhang, Lijun; Zhang, Shu; Liu, Shuhua; Hu, Xun
Abstract: Attapulgite (ATTP) is an abundant natural magnesium aluminosilicate mineral that can be used as support for manufacturing cost-effective solid acid catalysts. This study mainly focuses on structural change of ATTP and the formation of Brønsted and Lewis acid sites during sulfonation in H2 SO4 . The results indicate that the sulfonation leads to the drastic change of the crystal phases as sulfuric acid not only plays the roles of grafting the sulfur species but also reacts with the CaO, MgO, Al2 O3 and Fe2 O3 or their salts in ATTP to form the sulfates, resulting in the substantial change of the porous structure of ATTP. In such a process, the Brønsted acidic sites, which are the main active sites for the conversion of furfuryl alcohol (FA) to ethyl levulinate (EL), are introduced, while the abundance/strength of the Lewis acid sites are enhanced. The yield of EL up to 95.4% is achieved over the H2 SO4 /ATTP catalyst. The Fe2 (SO4 )3 and MgSO4 in the catalyst leaches in ethanol but does not affect the catalytic stability. The formed polymer also does not affect much the catalytic activity after their removal via the calcination in air. Graphical abstract: Image 1 Highlights: Sulfated attapulgite (ATTP) is prepared for conversion of furfuryl alcohol (FA) in ethanol. Sulfonation transforms CaO, MgO, Al2 O3 and Fe2 O3 phase, changing structure in ATTP. Sulfonation destroys Al–OH–Al, Si–O–Al and carbonate functionalities in ATTP. Sulfonation enhanced abundance/strength of Brønsted and Lewis acid sites. Leaching of sulfates does not affect the sulfur species that generate acidic sites.